2021
DOI: 10.1177/03000605211049960
|View full text |Cite
|
Sign up to set email alerts
|

Associations between traditional and non-traditional anthropometric indices and cardiometabolic risk factors among inpatients with type 2 diabetes mellitus: a cross-sectional study

Abstract: Objective We aimed to evaluate whether traditional and non-traditional adiposity indicators are associated with cardiometabolic risk factors among adult patients with type 2 diabetes mellitus (DM). Methods In this cross-sectional study among 240 inpatients with type 2 DM, we determined traditional anthropometric indicators including body mass index, waist circumference, hip circumference (HC), waist-to-hip ratio (WHR), waist-to-height ratio, and non-traditional anthropometric indicators including lipid accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…An increased CMI poses a risk for individuals with T2DM and is recognized as a detrimental factor. To effectively prevent the onset of T2DM, appropriate measures should be implemented to mitigate the escalation of the CMI from low to high values [ 15 , 16 ]. Additionally, the CMI exhibited positive correlations with diastolic blood pressure, systolic blood pressure, BMI, hip circumference, glucose (at 0 min), insulin (at 0 min), insulin (at 120 min), HOMA-IR, TC and PWV values.…”
Section: Discussionmentioning
confidence: 99%
“…An increased CMI poses a risk for individuals with T2DM and is recognized as a detrimental factor. To effectively prevent the onset of T2DM, appropriate measures should be implemented to mitigate the escalation of the CMI from low to high values [ 15 , 16 ]. Additionally, the CMI exhibited positive correlations with diastolic blood pressure, systolic blood pressure, BMI, hip circumference, glucose (at 0 min), insulin (at 0 min), insulin (at 120 min), HOMA-IR, TC and PWV values.…”
Section: Discussionmentioning
confidence: 99%
“…VAI, CVAI, TyG, and LAP are common obesity- and lipid-related indices that reflect the distribution of fat and indirectly glyco-metabolic ( 48 , 49 ). Our study also found that these indices are also sensitive predictors of hypogonadism in Chinese males with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a worldwide epidemic and leads to a 20% increased risk of acute myocardial infarction and obesity plays a major role in the development of T2DM. T2DM is a major risk factor for cardiovascular disease (20). Visceral obesity has been proven to be a more critical risk factor for T2DM (21).…”
Section: Discussionmentioning
confidence: 99%
“…Visceral adiposity index and LAP levels are very efficient in predicting cardiovascular disease risk factors in various clinical studies (20)(21)(22)(29)(30)(31). In people with T2DM and visceral obesity, lipid and lipoprotein metabolism problems are common, resulting in diabetic dyslipidemia and a high risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%